Neurotransmitter trafficking defect in a patient with clathrin (CLTC) variation presenting with intellectual disability and early-onset parkinsonism - Manti, Filippo; Nardecchia, Francesca; Blau, Nenad (Parkinsonism & related disorders, 2019)
Introduction - Clathrins play a key role in endocytosis, recycling, and trafficking as well as the generation of presynaptic vesicles. We report a new clinical condition associated with a de novo variant in the CLTC gene, which encodes the clathrin heavy polypeptide. - Case report - This 30-year-old woman presented with a developmental disorder during childhood that progressed to mild cognitive decline in late childhood and relapsing-remitting hypokinetic-rigid syndrome with severe achalasia, weight loss, and mood disorder in adulthood. 123I-Ioflupane SPECT was normal. Blood phenylalanine was slightly increased and PAH sequencing revealed compound heterozygosity for two variants, p.[Asp151Glu]:[Thr380Met]. CSF examination unexpectedly detected a remarkable reduction of homovanillic, 5-hydroxyindolacetic, and 5-methylthetrahydrofolic acids, which could not be ascribed to any alteration of tetrahydrobiopterin and related biogenic amine pathways. - Methods - Trio-based exome sequencing was performed. - Result - A de novo missense variant (c.2669C>T/p.Pro890Leu) was detected in CLTC. Treatment with biogenic amine precursors was ineffective, while the inhibitor of MAO-A selegiline resulted in persistent clinical improvement. - Conclusions - We suggest CLTC defect as a new disorder of biogenic amine trafficking, resulting in neurodevelopmental derangement and movement disorder. Neurotransmitter depletion in CSF may be a biomarker of this disease, and selegiline a possible treatment option.